2006
DOI: 10.1590/s0100-41582006000100004
|View full text |Cite
|
Sign up to set email alerts
|

Identificação de Pectobacterium carotovorum subsp. brasiliensis através de PCR-RFLP do gene recA

Abstract: Palavras-chave adicionais: pectobactérias, canela preta, podridão-mole, batata, Solanum tuberosum. ABSTRACT Identification of Pectobacterium carotovorum subsp. brasiliensis through PCR-RFLP of the rec-A genePectobacterium carotovorum subsp. brasiliensis has been proposed to be the major causal agent of blackleg of potato (Solanum tuberosum) in Brazil. In order to identify this subspecies, primers were selected from heterologous regions of recA genes present in P. carotovorum subsp. brasiliensis ATCC BAA-41, P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Knowledge of diversity is an important prerequisite for the identification of phytobacteria, as well as for taxonomic classifications, to support epidemiological studies and the development of strategies for plant diseases control, especially regarding selection of resistant varieties in breeding programs. This is particularly important when different closely related species and subspecies cause diseases in the same host, as is the case of pectobacteria in potatoes (EL TASSA; DUARTE, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of diversity is an important prerequisite for the identification of phytobacteria, as well as for taxonomic classifications, to support epidemiological studies and the development of strategies for plant diseases control, especially regarding selection of resistant varieties in breeding programs. This is particularly important when different closely related species and subspecies cause diseases in the same host, as is the case of pectobacteria in potatoes (EL TASSA; DUARTE, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Although 16S rDNA is relatively short and contains fewer phylogenetically informative characters than housekeeping genes often used in taxonomical studies (Ma et al , ), this gene sequences have several advantages, including being a highly conserved multicopy gene and easy to amplify. Genes encoding for rRNAs, heat‐shock proteins, ATPases, RNA polymerase and housekeeping genes, acnA , gapA , icdA , mdh , mtlD , pgi , proA and recA , have been successfully used to delineate phylogenetic relationships among bacteria (Ludwig & Schleifer, ; Santos & Ochman, ; El Tassa & Duarte, ; Ma et al , ). Waleron et al () demonstrated that the restriction fragment length polymorphism (RFLP) analysis of recA gene can act as a useful marker for identification of Pectobacterium and Dickeya , at both species and subspecies levels.…”
Section: Introductionmentioning
confidence: 99%